2005
DOI: 10.1007/s10531-004-6902-z
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Pressure and its Effects on Blood Parameters in a Stable and Dense Population of the Endangered Lesser Grey Shrike

Abstract: The risk that pathogens and parasites pose to endangered species is increasingly evident. Nonetheless, this is frequently overlooked when considering causes of decline of species and conservation practices. Here, we study the ecto and haemoparasites of adult and nestling Lesser grey shrikes Lanius minor from a dense and stable breeding population in central Europe and their effect on host blood parameters. We found three species of haemoparasites (Haemoproteus sp., microfilariae tentatively assigned to the fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
20
2
Order By: Relevance
“…, 2005), whereas others have reported no change (Shutler et al. , 1996; Ots & Hõrak, 1998; Valera et al. , 2005) or even increased levels (Dawson & Bortolotti, 1997; Johnsen & Zuk, 1998; Merino et al.…”
Section: Discussionmentioning
confidence: 96%
“…, 2005), whereas others have reported no change (Shutler et al. , 1996; Ots & Hõrak, 1998; Valera et al. , 2005) or even increased levels (Dawson & Bortolotti, 1997; Johnsen & Zuk, 1998; Merino et al.…”
Section: Discussionmentioning
confidence: 96%
“…Although the effect of parasites on other disease agents on shrikes has been scarcely documented (Lefranc and Worfolk 1997; but see Valera et al 2006), the available information are mainly records of parasite occurrence and taxonomic works (Hromada et al 2000;Skoracki et al 2001Skoracki et al , 2002Votypka et al 2003). We suggested that future studies on feather lice fauna should be done on wild, living birds and to link lice abundance with the shrikes' health status (for one exceptional example, see Valera at al.…”
Section: Discussionmentioning
confidence: 99%
“…To date however, knowledge of common parasites infecting birds is sometimes limited. This inhibits more detailed analysis and, hence, more data are still necessary (Lindell et al 2002;Valera et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies of threatened species can explore the effects of endemic parasites through experimental manipulation, thus most are limited to observational datasets to infer the costs of parasites to hosts (Valera et al 2006 ;Bunbury et al 2007Bunbury et al , 2008Zhang et al 2008). Since threatened species are often subjected to numerous sources of stress (Lafferty and Kuris, 1999), negative correlations between infection and body condition could have other causes.…”
Section: Impacts Of Parasites and Conservationmentioning
confidence: 99%